Studi Kinetika Pelindian Bijih Nikel Limonit Dari Pulau Halmahera Dalam Larutan Asam Nitrat [Kinetics Study of Nickel Limonite Ore Leaching from Halmahera Island in Nitric Acid Solution] - Mubarok, Mohammad Zaki; Fathoni, Muhammad Wildanil (Pusat Penelitian Metalurgi dan Material - LIPI, 2016)
One of the recent developments in the extraction of nickel from laterite ore by hydrometallurgical route is to use leaching reagent which can be regenerated, such as hydrochloric and nitric acids. Although the success of leaching of laterite ore has been reported, leaching kinetics study of laterite ore in nitric acid is stillpoorly published. In this paper, the results of leaching kinetics analysis of nickel laterite ore of limonite type from Halmahera Island in nitric acid solution at atmospheric pressure is discussed. The purposes of the kinetics study are to determine rate-determining step, kinetic parameters (i.e. reaction rate constant or diffusion coefficient), activation energy and the kinetics model. Leaching kinetics was studied by adopting shrinking core models (SCM). The analysis results reveal that the leaching rate of Halmahera limonite ore from Halmahera Island in nitric acid is controlled by diffusion through solid layer product with effective diffusion coefficient (De) of 2,1- 8,55 x 10-10 m2/s at the temperature range of 65-95 °C and activation energy of 46.78kJ/mol.AbstrakSalah satu perkembangan terkini proses ekstraksi nikel dari bijih laterit dengan jalur hidrometalurgi adalah dengan menggunakan reagen pelindi yang dapat diregenerasi, seperti asam klorida dan asam nitrat. Meskipun keberhasilan proses pelindian bijih nikel laterit dalam asam nitrat telah dipublikasikan, studi kinetika pelindian bijih nikel laterit dalam asam nitrat masih terbatas. Dalam paper ini dipresentasikan hasil analisis kinetika pelindian bijih nikel laterit tipe limonit dari Pulau Halmahera dalam larutan asam nitrat pada tekanan atmosfer. Studi kinetika pelindian bertujuan untuk mengetahui pengendali laju reaksi, parameter kinetika (konstanta laju reaksi atau koefisien difusi), energi aktivasi reaksi dan persamaan kinetikanya. Kinetika pelindian dipelajari dengan menggunakan model shrinking core (SCM). Hasil analisis menunjukkan bahwa pengendali laju reaksi pada pelindian bijih limonit dari Pulau Halmahera dalam larutan asam nitrat adalah difusi melalui lapisan produk padat yang tidak/belum bereaksi dengan koefisien difusi efektif (De) sebesar 2,1- 8,55 x 10-10 m2/s pada rentang suhu 65-95oC serta energi aktivasi sebesar 46,78 kJ/mol.